Multifrequency study of HH 137 and HH 138: discovering new knots and molecular outflows with gemini and APEX - Ferrero, Leticia V. (2020)
Fil: Ferrero, Leticia V. Universidad Nacional de Córdoba. Observatorio Astronómico de Córdoba; Argentina.